The Story Of The Batara Kala As A Foundation For The Creation Of The "Waktu Batu #3 Deus Ex Machina Dan Perasaan-Perasaan Padamu" By Teater Garasi (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2020)
Batara Kala as one of figure in Javanese mythology became the object of Teater Garasi’s creativity process.  Story of “Waktu Batu” was performed as the creation from Teater Garasi who used figure of Batara Kala. The research tried to explained exploration process of Teater Garasi towards story of Batara Kala as idea of theater perform creation. Finally, Waktu Batu becomes reperesntation story of Batara Kala in different form, especially theater performance until creating new discourse.